Réponses

  • Utilisateur Brainly
2013-05-11T19:49:50+02:00

p)

2(x+1)=7

2*x+2*1=7

2x+2=7

2x+2-2=7-2

2x=5

x=5/2

x=2.5

 

q)

3(x+2)=5(x+3)

3*x+3*2=5*x+5*3

3x+6=5x+15

3x+6-5x=5x+15-5x

-2x+6=15

-2x+6-6=15-6

-2x=9

x=9/-2

x=4.5

 

r)

4(x-1)=3(2x+2)

4*x+4*(-1)=3*2x+3*2

4x-4=6x+6

4x-4-6x=6x+6-6x

-2x-4=6

-2x-4+4=6+4

-2x=10

x=10/-2

x=-5

 

s)

4(2x+1)=2(2x+2)

4*2x+4*1=2*2x+2*2

8x+4=4x+4

8x+4-4x=4x+4-4x

4x+4=4

4x+4-4=4-4

4x=0

x=0/4

x=0

 

t)

3x+4=7-x

3x+4+x=7-x+x

4x+4=7

4x+4-4=7-4

4x=3

x=3/4

x=0.75